2006
DOI: 10.1127/0029-5035/2006/0083-0253
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton composition and distribution along the Albanian coast, South Adriatic Sea

Abstract: The present study was conducted within the framework of the INTERREG II Italy-Albania Project. Water samples were collected during two cruises carried out in October 2000 and April 2001. This study represents the first survey of the phytoplankton assemblages along the entire Albanian coast in the South Adriatic Sea. A total of 119 counting categories were recorded; 98 of them were identified to the species level, 13 to the genus level, while 8 remained undetermined. The Shannon diversity index (H') an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Wind stress and along-coast currents regulate offshore cross-shelf transport of phytoplankton-rich waters (Martinez-Lopez and Zavala-Hidalgo 2009). We recorded relatively low concentrations of nutrients, similar to those recorded in October 2000 and April 2001 (Saracino and Rubino 2006) and in the Otranto Strait (Viličić et al 1995;Socal et al 1999). TIN/PO 4 molar ratio ranged from 39 to 1,389, with an average of 330, indicating phytoplankton growth limited by phosphorus at all stations (much more at offshore stations; Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Wind stress and along-coast currents regulate offshore cross-shelf transport of phytoplankton-rich waters (Martinez-Lopez and Zavala-Hidalgo 2009). We recorded relatively low concentrations of nutrients, similar to those recorded in October 2000 and April 2001 (Saracino and Rubino 2006) and in the Otranto Strait (Viličić et al 1995;Socal et al 1999). TIN/PO 4 molar ratio ranged from 39 to 1,389, with an average of 330, indicating phytoplankton growth limited by phosphorus at all stations (much more at offshore stations; Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Although the role of the Po River is relatively well understood, the southeastern Adriatic (Albanian) rivers have not been seriously considered to date, neither as a physical force, nor as a nutrient source. Besides studies on phytoplankton size structure , taxonomic composition, and diversity (Saracino and Rubino 2006;Vadrucci et al 2008) in the southeastern Adriatic, there is no information on fine distribution of plankton across the Albanian shelf and continental slope, where a distinct hydrographic boundary between north westerly inflowing current from the Ionian Sea and the low salinity Albanian coastal waters can be frequently detected by satellite imagery. The discharge of rivers into the Adriatic Sea, the strong northern wind (the bora), and currents participate in the formation of fronts in the northern Adriatic (Lee et al 2005) and along the Albanian shelf (Le Vourch et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The NANO-dominated phytoplankton consisted mostly of phytoflagellates measuring less than 10 mm, as is generally the case throughout the Adriatic (Saracino and Rubino, 2006). Chroococoid cyanobacteria were the major NANO from May to October, reaching 2.9 x 10 7 cells L -1 in July, the period of N limitation.…”
Section: Discussionmentioning
confidence: 75%
“…For example, in the Indian Ocean, Bhat and Matondkar (2004) noted the occurrence of C. polykrikoides in the coastal waters of Goa, India, while Ramaiah et al (2005) reported blooms along the Malabar Coast of India. Large blooms of C. polykrikoides have also been recently noted in the Black Sea (Vershinin et al, 2004(Vershinin et al, , 2005Terenko, 2005), Croatian coastal waters of the Adriatic Sea (Saracino and Rubino, 2006) and in the Mediterranean across the Gulf of Olbia (coastal Italy; Sannio et al, 1997). One of the more significant HAB events of the last decade occurred throughout the Arabian Gulf and Gulf of Oman from 2008 through 2009 when a massive bloom of C. polykrikoides caused fish kills, the death of coral reefs, and disruption of desalination plants in Iran, Saudi Arabia, and the United Arab Emirates (Richlen et al, 2010).…”
Section: Distribution and Expansion Of Cochlodinium Bloomsmentioning
confidence: 91%